Skull anatomy and neuromorphology of Hypsosteiromys , a Colhuehuapian erethizontid rodent from Argentina - Dozo, Maria Teresa (2004)
A relatively complete skull of Hypsosteiromys with a well-preserved natural endocranial cast was recovered from the Colhuehuapi Member (lower Miocene, Sarmiento Formation) at Gran Barranca, Chubut Province, Argentina. This is the only known skull of this genus. It differs from the other erethizontids because it is all along very low, the ascending ramus of the premaxillae extends behind the posterior margins of the nasals, and the external auditive meatus has a ventral furrow. Comparison of the endocast with the brains of extant Erethizontidae demonstrates remarkable neuro-morphological homogeneity, despite differences in size. Erethizontid´s brains have rounded telencephalic hemispheres with prominent frontal lobes and small olfactory bulbs, and lack temporal lobes and neocortical sulci. Thus, the Gran Barranca skull shows that the external neuromorphology of the Erethizontidae has not changed substantially at least since the early Miocene.